2021
DOI: 10.1002/jcop.22718
|View full text |Cite
|
Sign up to set email alerts
|

A culturally targeted video to promote genetic counseling in a community sample of at‐risk US Latina women: The role of the concrete mindset

Abstract: Latina women, who are at increased risk of hereditary breast and ovarian cancer (HBOC), have lower use of genetic counseling and testing (GCT) than non‐Hispanic White women. In a recent study, culturally targeted video improved psychosocial outcomes related to GCT. Additional analyses examine whether the culturally targeted video improved positive reactions in women who focus on difficulties (concrete mindset) versus women who focus on the final goals (abstract mindset). Participants (N = 32) completed surveys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…With the service delivery aspect of the process addressed, greater attention could then be paid to those referred to genetic counseling. Prior work has documented that approaches such as culturally appropriate narrative decision aid videos increase knowledge and positive attitudes toward and intentions to attend genetic counseling 29–32 . These approaches could be included in future studies that focus directly on individuals at high risk for cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the service delivery aspect of the process addressed, greater attention could then be paid to those referred to genetic counseling. Prior work has documented that approaches such as culturally appropriate narrative decision aid videos increase knowledge and positive attitudes toward and intentions to attend genetic counseling 29–32 . These approaches could be included in future studies that focus directly on individuals at high risk for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…proaches such as culturally appropriate narrative decision aid videos increase knowledge and positive attitudes toward and intentions to attend genetic counseling. [29][30][31][32] These approaches could be included in future studies that focus directly on individuals at high risk for cancer.…”
Section: Testmentioning
confidence: 99%
“…En apoyo de las predicciones de las dos teorías mencionadas, AIT y CLT, sobre los comportamientos de riesgo para la salud, investigaciones anteriores han mostrado que el estilo de pensamiento concreto está relacionado con problemas de autocontrol (Caballero et al, 2021; Fujita, 2008, 2011; Fujita & Carnevale, 2012; Fujita & Han, 2009). Sin embargo, un estilo abstracto fomenta mayor autocontrol, lo que facilita la adopción de comportamientos exigentes con beneficios a largo plazo (e.g., Aguilar et al, 2020; Carrera et al, 2020, 2021). En coherencia con estos resultados, se ha relacionado el estilo abstracto con un mayor bienestar percibido (véase Horvath, 2018), incluso en situaciones de amenaza grave como el vivir en situación de escasez económica (Aguilar et al, 2020) o bajo amenaza terrorista (Fernández et al, 2020).…”
Section: ¿Salud O Riqueza? La Influencia De Las Amenazas Percibidas C...unclassified
“…Supporting the AIT’s and CLT’s predictions regarding health-risk behaviours, previous research has shown that the concrete style is associated with self-control problems (Caballero et al, 2021; Fujita, 2008, 2011; Fujita & Carnevale, 2012; Fujita & Han, 2009). However, an abstract style promotes greater self-control, which facilitates the adoption of demanding behaviours with long-term benefits (e.g., Aguilar et al, 2020; Carrera et al, 2020, 2021). Consistent with these findings, the abstract style has also been associated with greater perceived well-being (see Horvath, 2018), even under situations of severe threat, such as living in economic scarcity (Aguilar et al, 2020) or under terrorist threat (Fernández et al, 2020).…”
mentioning
confidence: 99%